Disclosure and Nondisclosure Among People Newly Diagnosed with HIV: An Analysis from a Stress and Coping Perspective - Hult, Jen R. (Mary Ann Liebert, Inc., 2012)
Disclosing HIV status to friends, family, and sex partners is often stressful. However, HIV disclosure has been associated with improved physical health, psychological well-being, and improved health behaviors. The aim of this study was to address some of the gaps in the literature regarding the disclosure process by conducting a mixed-methods study of disclosure in people newly diagnosed with HIV and the relationship of disclosure to stigma and social support. The CHAI (Coping, HIV, and Affect Interview) Study was a longitudinal cohort study that followed individuals who were newly diagnosed with HIV. The study took place from October 2004 to June 2008 in the San Francisco Bay Area. This sample includes data from 50 participants who were interviewed 1, 3, and 9 months following diagnosis with HIV. We identified four main approaches to HIV disclosure that revealed distinct differences in how participants appraised disclosure, whether disclosure was experienced as stressful, and whether disclosure or nondisclosure functioned as a way of coping with an HIV diagnosis. Implications of these findings for disclosure counseling are discussed.